An Unclear Relationship Between Idiopathic Non-Cirrhotic Portal Hypertension, Pyogenic Liver Abscess, Or Portal Vein Thrombosis - Kilani, Yassine; Miller, MD, Dwayvania; Jamil, MD, Muhammad Aqib; Kamal MD, Syeda Duaa; Yao, MS, Albert; Ackerman, MS, Henry; Pillai, MD, Anjana; Azeez, MD, Sulaiman (International Journal of Innovative Research in Medical Science, 2024)
Background: Pyogenic liver abscess (PLA) remains rare in the United States (US). Data shows that Klebsiella pneumoniae is becoming the leading bacterial cause of PLA. Causes of bacterial seeding in the liver include biliary tract pathology, portal vein bacteriemia, systemic bacteremia, penetrating wounds, or liver surgery. We describe a case of cryptogenic Klebsiella pneumoniae PLA, associated with an incidental finding of idiopathic non-cirrhotic portal hypertension (INCPH). Case presentation: A 55-year-old female, with no past medical history, presented with 7 days of nocturnal fever, dry cough, mild back pain, and jaundice. On admission, she was febrile, tachycardic, and jaundiced. The abdomen was soft, non-tender and Murphy’s sign was negative. Laboratory workup revealed normocytic anemia, leukocytosis with neutrophilia, and evidence of cholestasis. Imaging with liver ultrasound (US), Computer Tomography (CT), and Magnetic Resonance Imaging (MRI) showed a heterogeneous cystic mass in the left hepatic lobe, heterogeneous hepatic parenchyma, and a large stone in the fundus of the gallbladder without evidence of cholecystitis, along with signs of portal hypertension (PHTN). CT-guided drainage showed purulent fluid. The patient was treated with antibiotics. Klebsiella was isolated in both blood and pus cultures. Further workup for liver disease was inconclusive. A liver biopsy showed evidence of non-cirrhotic portal fibrosis (NCPF). Conclusions: The incidental discovery of PHTN in patients with underlying liver disease should prompt a full diagnostic workup. Diagnosis of INCPH requires clinical signs of PHTN, patent portal veins on imaging, exclusion of cirrhosis on liver biopsy, and exclusion of chronic liver disease that might cause either cirrhosis or NCPF. The management of INCPH, regardless of the cause, involves reducing the portal pressure.